Productivity of tomato according to phosphorus doses - Siegfried Mueller, Siegfried (2020)
During the growing seasons 2007/08 and 2008/09, experiments were carried out under field conditions at Epagri - ExperimentalStation of Caçador, SC, to evaluate the effect of P2O5 fertilization on tomato productivity, in a no-till system. The CompleteRandom Block design contained five levels of P2O5 (0, 250, 500, 750 e 100 kg ha-1), with five replications. The phosphorus sourcewas triple superphosphate. For the total productivity, commercial, and extra AA, there was Quadratic effects in response todoses of P applied in the two crops. The METs of commercial productivity were achieved with 850 and 885 kg ha-1 P2O5 andMEEs with 710 and 827 kg ha-1 of P2O5 for crops 2007/08 and 2008/09 respectively. The average weight of marketable fruits andextra AA fruits, showed only effect of P2O5 levels in 2008/09, i.e., when the soil contained low levels of P.